UTILITARIAN SHOPPING VALUE AND HEDONIC SHOPPING VALUE TO IMPROVE CUSTOMER SATISFACTION AND REPURCHASE INTENTION ON E-COMMERCE BUSINESS - Andriani, Nova; Mugiono, Mugiono; Rahayu, Mintarti (Universitas Brawijaya, Indonesia, 2021)
This study aims to examine and analyze the relationships between motivation shopping value, repurchase intention, and customer satisfaction on Lazada Indonesia's ecommerce consumers in Malang City. The population of this research is Lazada Indonesia consumers who are of productive age (19-34 years old) in Malang City and the number of samples obtained following the research criteria is 100 correspondents. Sample selection is done by the non-probability sampling technique with the purposive sampling method. The research instrument used was a questionnaire that was analyzed using smartPLS 2.0 software. The results of this study indicate that utilitarian shopping value and hedonic shopping value have a direct effect on customer satisfaction and repurchase intention. Meanwhile, indirectly hedonic shopping value did not affect repurchase intention through customer satisfaction.